Double homozygosity in CEP57 and DYNC2H1 genes detected by WES: Composite or expanded phenotype?. Issue 3 (14th January 2020) - Pezzani, Lidia; Pezzoli, Laura; Pansa, Alessandra; Facchinetti, Barbara; Marchetti, Daniela; Scatigno, Agnese; Lincesso, Anna R.; Perego, Loredana; Pingue, Monica; Pellicioli, Isabella; Migliazza, Lucia; Mangili, Giovanna; et al.
Abstract: Background: In the last few years trio‐whole exome sequencing (WES) analysis has demonstrated its potential in obtaining genetic diagnoses even in nonspecific clinical pictures and in atypical presentations of known diseases. Moreover WES allows the detection of variants in multiple genes causing different genetic conditions in a single patient, in about 5% of cases. The resulting phenotype may be clinically discerned as variability in the expression of a known phenotype, or as a new unreported syndromic condition. Methods: Trio‐WES was performed on a 4‐month‐old baby with a complex clinical presentation characterized by skeletal anomalies, congenital heart malformation, congenital hypothyroidism, generalized venous and arterial hypoplasia, and recurrent infections. Results: WES detected two different homozygous variants, one in CEP57, the gene responsible for mosaic variegated aneuploidy syndrome 2, the other in DYNC2H1, the main gene associated with short‐rib thoracic dysplasia. Conclusion: The contribution of these two different genetic causes in determining the phenotype of our patient is discussed, including some clinical signs not explained by the detected variants. The report then highlights the role of WES in providing complete and fast diagnosis in patients with complex presentations of rare genetic syndromes, with important implications in the assessment of recurrence risk. Abstract : Whole exome sequencing (WES) allows the detection of variants in multiple genes causing different genetic conditions in a single patient. The resulting phenotype may be clinically discerned as variability in the expression of a known phenotype, or as a new unreported syndromic condition. Trio‐WES was performed in a 4 months patient with complex clinical presentation, and detected two different homozygous variants, one in CEP57, the gene responsible of mosaic variegated aneuploidy syndrome 2, the other in DYNC2H1, the main gene associated with short‐rib thoracic dysplasia. The contribution of these two different genetic causes in determining the phenotype of our patient is discussed, including some clinical signs not explained by the detected variants.